震災前後の福島県内小学生の体力・運動能力の変化: 平成22、23 年度の体力・運動能力テスト結果の比較 - 菅家, 礼子; 小川, 宏 (スポーツ教育学研究, 2018)
Because of the nuclear power plant accident caused by the East Japan great earthquake disaster, occurring in Fukushima in March 2011, radiation material spread, resulting in outdoor activity being limited and/or avoided for a period of six months to one year, in elementary schools in Fukushima.As such, the purpose of the current research was to examine changes of physical and motor ability of schoolchildren in Fukushima before and after the earthquake disaster, and to clarify the influence of limited outdoor activity and indoor effort at school to schoolchildren at that time.Results of change of physical and motor ability of schoolchildren in Fukushima after the earthquake disaster were as follows:1.Schoolchildren of upper grades displayed decreased 20-m shuttle run(endurance). 2. Standing broad jump ability (jumping ability) for boys of lower grades, and softball throwing for distance (ball throwing ability) declined. 3.Grip strength (muscle strength) and sitting trunk flexion (flexibility) showed improvement. 4.Repeated side-stepping (agility) in the lower grades was also improved.By the influence of limited outdoor activity, physical and motor ability, such as endurance and ball throwing for distance, which should be trained outdoors declined. Conversely, by the deliberate effort, such as grip strength (muscle strength) and sitting trunk flexion (flexibility), which practiced within the gymnasium improved.